Alpha acids content in Czech hops from the 2023 harvest – forecasts, reality and trends - Krofta, Karel; Mikyška, Alexandr; Fritschová, Gabriela; Kroupa, František; Tichá, Jana (KVASNY PRUMYSL, 2024)
The most important weather factor for the hop growing season in 2023 was the rainy period in the last decade of July and the first decade of August, which replaced the previously warm and dry weather. Heavy rainfall with a total of 60–100 mm of water and temperatures in the range of 20–25 °C saved the annual hop harvest from the yield decline that occurred in 2022. However, the above-average harvest of nearly 7000 tonnes and a yield of 1.44 t/ha was achieved at the expense of the bitter compound content of most varieties. The alpha acid content of Saaz hops was well below 3.0% w/w in all hop-growing regions, one of the lowest levels for the last 10 years. It is even lower than the extremely hot and dry year 2022 and comparable to 2015. Lower levels of alpha acids were also found in Sládek (4.8–6.7% w/w), Premiant (6.9–7.9% w/w) and Saaz Special (4.3% w/w). The varieties Agnus, Rubín and Vital contained stable amounts of alpha acids in the range of 11–13% w/w, which is about the same as in previous years. The total production of alpha acids in Czech hops from the 2023 harvest was 253 tons, which is average in a longerterm comparison. Saaz hops accounted for only 55% of the total production, although they are grown on 83.3% of the harvest area.